Veronicastrum axillare Alleviates Ethanol-Induced Injury on Gastric Epithelial Cells via Downregulation of the NF-kB Signaling Pathway - Wei-chun Zhao; Yan-shan Xu; Gang Chen; Yan Guo; Dan-yi Wang; Gui-bin Meng (Gastroenterology Research and Practice)
We used human gastric epithelial cells (GES-1) line in an ethanol-induced cell damage model to study the protective effect of Veronicastrum axillare and its modulation to NF-κB signal pathway. The goal was to probe the molecular mechanism of V. axillare decoction in the prevention of gastric ulcer and therefore provide guidance in the clinical application of V. axillare on treating injuries from chronic nephritis, pleural effusion, gastric ulcer, and other ailments. The effects of V. axillare-loaded serums on cell viability were detected by MTT assays. Enzyme-linked immunosorbent assay (ELISA) and Real-Time PCR methods were used to analyze the protein and mRNA expression of TNF-α, NF-κB, IκBα, and IKKβ. The results showed that V. axillare-loaded serum partially reversed the damaging effects of ethanol and NF-κB activator (phorbol-12-myristate-13-acetate: PMA) and increased cell viability. The protein and mRNA expressions of TNF-α, NF-κB, IκBα, and IKKβ were significantly upregulated by ethanol and PMA while they were downregulated by V. axillare-loaded serum. In summary, V. axillare-loaded serum has significantly protective effect on GES-1 against ethanol-induced injury. The protective effect was likely linked to downregulation of TNF-α based NF-κB signal pathway.